Integration of patient-reported outcomes into survivorship care. Issue 28 (1st October 2022) - Gilmore, Katherine Ramsey; Chapman, Patricia Hansberry; Rollins, Johnny; Lee-Kim, Soo; Robinson, Justine; Mullen, Ellen; Mistry, Haleigh; Singh, Prachee; Coyne, Robin; Nelson, Ana; Osai, William; Stolar, Karen; et al.
Abstract : 271 Background: Patient reported outcomes (PRO) can be valuable clinical tools to embed the voice of patients into the clinical experience. The use of PROs in the context of cancer survivorship is relatively under-explored. Methods: Disease-specific modules of the MD Anderson Symptom Inventory (MDASI) PRO were integrated into the electronic health record (EHR), and distributed 3-7 days prior to survivorship clinic visits through the patients' EHR portal. Patients with virtual visits were called 24 hours prior, instructed how to video link, and how to complete the MDASI PRO. For patients who completed the PRO electronically, results were reviewed during clinic visit. High symptom alerts (> = 7) for four key symptoms were established and triggered an automatic message to care teams for review. Results: From Sept 1, 2020 – August 31, 2021, 2, 196 PRO surveys were sent to patients with 1, 268 submitting results (57.74%) (see Table). Within specific clinics, the submission rates varied greatly between in-person and virtual appointments (33% vs. 83%). Submission rates varied by clinics, with responses ranging from 28.57% - 73.59%. Clinics with higher overall rates had a higher proportion of virtual visits. Conclusions: Electronic distribution of PROs can be successfully integrated into long term survivorship clinic visits. Virtual visits had overall much higher PRO response rates, due to pre-visit workflows which encouraged the completion of PROs. We conclude that patient education and real time support is needed to facilitate patients' completion of PRO surveys through the electronic portal.Patient reported outcomes submission rates by clinic (Sept 1, 2020 – August 31, 2021). Clinic # Submitted - Virtual Appt # Sent - Virtual Appt % Submitted - Virtual Appt # Submitted - In Person Appt # Sent - In Person Appt % Submitted - In Person Appt Total % Submitted - All Appt Breast 0 0 N/A 23 82 28.05% 28.05% GU 185 267 69.29% 11 39 28.21% 64.05% Head & Neck 107 116 92.24% 128 477 26.83% 39.63% Lymphoma 0 0 N/A 24 73 32.88% 32.88% Stem cell transplant 6 13 46.15% 52 130 40.00% 40.56% Thoracic 1 1 100.00% 1 6 16.67% 28.57% Thyroid 600 681 88.11% 130 311 41.80% 73.59% Grand Total 899 1078 83.40% 369 1118 33.01% 57.74%